An investigation of LytE in fulfilling the D,L-endopeptidase requirement for viability of Bacillus subtilis - Uelze, Laura (Trinity College (Dublin, Ireland). Department of Genetics, 2016)
The bacterial cell wall determines cell shape, resists turgor pressure, provides a microclimate between the cell and the external milieu and acts as a platform for the exposure of cellular proteins. The cell wall is a dynamic structure with constant synthesis and turnover to accommodate the remodelling that is required during cell growth and division. Autolysins play a key role in cell wall remodelling, with 6. subtilis encoding 35 such enzymes. Redundancy of enzymatic activity is a notable feature of this enzyme complement. For example, there are 7 D,L-endopeptidases (CwlO, CwlS, LytE, LytF, PgdS, YkfC, YqgT) encoded in the B. subtilis genome. Although none of the autolysins in B. subtilis is essential for viability, the CwlO and LytE D,L-endopeptidases are synthetically lethal. This is an especially interesting finding, since CwlO and LytE differ completely in the domains outside of the catalytic domain. The N-terminal domain of CwlO has a coiled-coil structure that interacts with the membrane embedded FtsEX complex, whereas LytE has 3 LysM motifs that bind to peptidoglycan.
Keywords: Genetics & Microbiology, Ph.D.; PhD Trinity College Dublin, 2016